Applied Theatre: Understanding Change (Landscapes: the Arts, Aesthetics, and Education,, 2018)
This volume offers researchers and practitioners new perspectives on applied theatre work, exploring the relationship between applied theatre and its intent, success and value. Applied theatre is a well-established field focused on the social application of the arts in a range of contexts including schools, prisons, residential aged care and community settings. The increased uptake of applied theatre in these contexts requires increased analysis and understanding of indications of success and value. This volume provides critical commentary and questions regarding issues associated with developing, delivering and evaluating applied theatre programs. Part 1 of the volume presents a discussion of the ways the concept of change is presented to and by funding bodies, practitioners, participants, researchers and policy makers to discover and analyse the relationships between applied theatre practice, transformative intent, and evaluation. Part 2 of the volume offers perspectives from key authors in the field which extend and contextualize the discussion by examining key themes and practice-based examples. .